2021
DOI: 10.1007/s11548-021-02404-2
|View full text |Cite
|
Sign up to set email alerts
|

Mask then classify: multi-instance segmentation for surgical instruments

Abstract: Purpose The detection and segmentation of surgical instruments has been a vital step for many applications in minimally invasive surgical robotics. Previously, the problem was tackled from a semantic segmentation perspective, yet these methods fail to provide good segmentation maps of instrument types and do not contain any information on the instance affiliation of each pixel. We propose to overcome this limitation by using a novel instance segmentation method which first masks instruments and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…As opposed to standard laparoscopy, robotic-assisted surgery that uses complete robotic surgical systems has the capacity to record and interpret data regarding instrument location into DL algorithms. These types of data are referred to as instrument priors can enhance a robots ability to accurately identify robotic surgical instruments and even their respective parts [31]. As instrument segmentation has evolved, researchers have shown that algorithms can be developed that can even correctly interpret datasets that are publicly available and not only datasets obtained locally under controlled environments.…”
Section: Instance/video/surgical Segmentationmentioning
confidence: 99%
“…As opposed to standard laparoscopy, robotic-assisted surgery that uses complete robotic surgical systems has the capacity to record and interpret data regarding instrument location into DL algorithms. These types of data are referred to as instrument priors can enhance a robots ability to accurately identify robotic surgical instruments and even their respective parts [31]. As instrument segmentation has evolved, researchers have shown that algorithms can be developed that can even correctly interpret datasets that are publicly available and not only datasets obtained locally under controlled environments.…”
Section: Instance/video/surgical Segmentationmentioning
confidence: 99%
“…They evaluated their architecture on the EndoVis17 and an in-house hysterectomy dataset. Kurmann et al (2021) proposed a encoder-decoder network for segmentation and classification of surgical instruments in endoscopic images. Their "segment first, classify last" approach used a shared encoder, two decoders for instance segmentation, and a classifier for instance classification, and it provided good results on the EndoVis 2017 dataset.…”
Section: Tool Segmentation Researchmentioning
confidence: 99%
“…Ni et al (2020) propose a bilinear attention network with an adaptive receptive field to tackle the challenges of scale and illumination inter-frames variability. Kurmann et al (2021) propose an alternative to standard semantic segmentation, first extracting instrument instances and then independently classifying them, reaching state-of-the-art results for this task. Despite the good results obtained by fullysupervised methods, their application is inherently limited by the need for manual annotations, which prevents their scalability.…”
Section: Surgical Tool Segmentationmentioning
confidence: 99%